A European consistency for functioning of RECs? We just lost our chance. Issue 6 (8th December 2012) - Waligora, Marcin
Abstract : On 17 July 2012, the European Commission formally adopted a proposal for a new European Union (EU) Directive regarding clinical trials, which will repeal and replace the existing Directive 2001/20/EC. The main reasons for the revision were: (1) the decreasing number of clinical trials in the region and (2) harsh criticism of the present version of the Directive. The proposed regulation could simplify the rules for conducting clinical trials and also rebuild the entire system of clinical trial assessment. However, it seems that we probably have already lost our chance regarding the consistency and quality of functioning of research ethics committees in the EU.